課程研究現代化：內涵的演變 ──三十年中國內地課程研究歷程The Evolution on the Modernization of Curriculum Research: The Course of China's Curriculum Research During the 30-year - 劉徽Hui Liu (Higher Education Foundation, 2009)
改革開放三十年是中國內地課程研究蓬勃發展的三十年，綜觀這三十年課程領域的概念演化，不難發現，「現代化」是一個貫穿其中的概念，課程研究的現代化歷程是指課程研究領域的「不斷超越」的品質，從1980年代「構建課程工程話語」到1990年代「反思基礎上課程論學科的知識化和專業化」到2000年後創建「跨學科的課程論學科框架」，課程研究現代化隨著時代和課程現代化內涵的演變不斷地發生變化。 Curriculum research has a fast development during China's 30-year reform. Reviewing and reflecting the 30-year curriculum research development, we find the dominant word "modernization". The modern evolution of curriculum research is defined as surpassing ceaselessly. In the 1980's, it is characterized by establishing a rigorous curriculum engineering system. In the 1990's, it is characterized by the knowledgelization and specialization of curriculum development based on reflection. In the new millennium, it is characterized by the reconstruction of the basic structure of curriculum study under the background of cross discipline.